A Reconnaissance Geophysical Survey of the Kawartha Lakes and Lake Simcoe, Ontario - Todd, Brian; Lewis, C. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1993)
ABSTRACTA marine geophysical survey program has been conducted in lakes of southern Ontario. The survey was designed to detect neotectonic features, if they exist, and to evaluate their geological importance. High-resolution single- and multichannel seismic reflection profiling were used to delineate late- and post-glacial sedimentary strata and structures, as well as the sediment/bedrock interface, in the Kawartha Lakes and Lake Simcoe. Results show that two seismostratigraphic sequences are common within the unconsolidated overburden. The lower unit exhibits a parallel reflection configuration having strong reflection amplitudes, whereas the upper unit is acoustically transparent and overlies the lower unit conformably in some places and unconformably in others. Both units vary in thickness within lakes and from lake to lake. Typical subbottom profiles of Precambrian rock surfaces are rolling; those of Paleozoic rock surfaces are smooth. At one location in Lower Buckhorn Lake, tilted rock surfaces may be faulted but disturbance of overlying glacioge-nic sediments was not observed. In western Lake Simcoe and Kempenfelt Bay, slumping into graben-like features was observed. Also in Lake Simcoe, a diapiric feature was documented. It is speculated that these disturbances most likely result from glacier ice block melting and fluid migration. A tectonic origin, however, cannot be discounted at this stage of investigation. Additional systematic marine geophysical surveys are required in the future to map features in detail to determine whether they are of neotectonic or glaciotectonic origin.